Perbandingan Penyelesaian Keberatan dan Banding Pajak di Amerika Serikat, Australia dan Indonesia - Mulyono Mulyono; Manotar Tampubolon; Serirama Butarbutar (Syntax Corporation Indonesia, 2024)
The research was conducted using normative legal research methods, which were carried out through literature research and literature studies and the approach used in conducting this research was a statutory approach and a conceptual approach, to elements in the tax law system. The research found that the position of the Fiscus in Indonesia which has absolute power in determining the amount of tax and decisions on taxpayer objections according to Law Number 28 of 2007 does not provide fair legal certainty and does not reflect the principle of equal legal position as stipulated in Article 27 paragraph (1) of the 1945 Constitution, because of the risk of tax penalties of 30% to 100% due to defeat in objections and appeals. Unlike the United States, which has three tax courts with FOI principles, and Australia, which provides neutral mediation through the ATO and internal and external settlement channels, Indonesia needs to improve fiscal justice by fulfilling taxpayers' rights such as the rights to information, guidance, hearing, appeal, certainty, privacy, and confidentiality. The principles of fairness, effectiveness, and ease of administration are important to increase tax capacity and ensure taxpayers can carry out their obligations properly.